The Effect of Nutritional Status, Level of Physical Activity and Hemoglobins on Physical Endurance - Moh Nanang Himawan Kusuma; Muhamad Syafei; Didik Rilastiyo (JUARA : Jurnal Olahraga, 2019)
Technological developments have an impact on increased consumption of junk food. On the other hand, the change was also followed by nutritional problems which later became a trigger factor for the increasing prevalence of physical inactivity which had an impact on the increase in hypokinetic disease and metabolic syndrome problems. The Problems related to nutritional status and decrease in physical activity can cause a decrease in cardiorespiratory ability, which is influenced by hemoglobin levels.Purposes: To determine the relationship of nutritional status, physical activity and hemoglobin levels on cardiorespiratory. Methods: Observational analytic with cross sectional approach in 47 male students using inclusion criteria (PAR-Q) supplemented by ethical clearance. Hemoglobin levels were measured by cyanmethemoglobin, nutritional status (BMI), physical activity (IPAQ), while VO2max with MFT. Bivariate analysis using Pearson product moment, multiple regression analysis was performed using correlation test.Findings: Nutritional status had low effect with a contribution of 13.6%, physical activity has moderate with contribution of 21.3%, and hemoglobin levels had a strong effect with 32.1% contribution to cardiorespiratory ability. Conclusion: Nutritional status, physical activity, and hemoglobin levels have an influence on cardiorespiratory ability, where the hemoglobin level has the highest contribution then followed by physical activity and nutritional status.